TRACE METALS IN SURFACE SEAWATERS IN THE RED SEA AND GULF OF ADEN-YEMEN - Al-qadasy, Mohammed Kassem Othman; Babaqi, Abdulla Saleh; Al-Abyadh, Mukhtar Mohammed; Al-kaf, Ali Gamal Ahmed (Universal Journal of Pharmaceutical Research, 2017)
Objectives: The present work has been done considering the constant spread pollution of heavy metals in water bodies. Pollution among water bodies is a major global problem. This contaminates not only the water but also the sediment and aquatic life such as fish. The water samples were collected from the three different Cities of Yemeni coasts. Aden, Al-Hodeidah and AL-Mukalla were chosen for the sample collection. Methods: The study was carried out in the all three seasons of winter 2011, summer 2012 and winter 2013 in order to check seasonal variation of heavy metal pollution.Total 81 samples of each Water were analyzed. The four heavy metals lead, Cadmium, Mercury and arsenic which are considered highly toxic were detected in the samples in the year 2010, 2012 and 2013. The heavy metal concentrations in the samples were measured using the Atomic Absorption Spectrophotometer. Results: The obtained results showed that the concentration (mg/l) of the heavy metal in seawater (Pb-0.061±0.005, Cd-0.007±0.001, Hg-0.007±0.0005 and As-0.008±0.0003) mg/l. The obtained results showed that the heavy metals concentrations were significantly higher, during the summer season for seawater samples in all stations during the study period. Because of the frequent use of water in the hot summer, results in an increase in sewage, as well as to the high rate of environmental variables in the summer. Conclusion: By comparing the results obtained with other data obtained from the local and international studies, in addition to, comparing the results standard levels of these metals contaminated and adopted internationally and domestically and the pollution levels in Yemen is currently within the lower limits of pollution. However, the study recommends continuing the study of these pollutants and other contaminants and their impact on the environment and marine life especially invertebrates. Peer Review History: Received 2 October 2017; Revised 7 November; Accepted 30 December, Available online 15 January 2018 Academic Editor: Dr. Asia Selman Abdullah , Al-Razi university, Department of Pharmacy, Yemen, asia_abdullah65@yahoo.com Reviewer(s) detail: Dr. Asia Selman Abdullah , Al-Razi university, Department of Pharmacy, Yemen, asia_abdullah65@yahoo.com Essam Mohamed Eissa , Beni-Suef – 32 Tahrir St, Egypt, dressamceutics@yahoo.com